Eliminating child labour in Malawi: a British American Tobacco corporate responsibility project to sidestep tobacco labour exploitation. Issue 3 (25th May 2006) - Otañez, M G; Muggli, M E; Hurt, R D; Glantz, S A
Abstract : Objectives: To examine British American Tobacco and other tobacco industry support of the Eliminating Child Labour in Tobacco Growing Foundation. Design: Analyses of internal tobacco industry documents and ethnographic data. Results: British American Tobacco co-founded the Eliminating Child Labour in Tobacco Growing Foundation (ECLT) in October 2000 and launched its pilot project in Malawi. ECLT's initial projects were budgeted at US$2.3 million over four years. Labour unions and leaf dealers, through ECLT funds, have undertook modest efforts such as building schools, planting trees, and constructing shallow wells to address the use of child labour in tobacco farming. In stark contrast, the tobacco companies receive nearly US$40 million over four years in economic benefit through the use of unpaid child labour in Malawi during the same time. BAT's efforts to combat child labour in Malawi through ECLT was developed to support the company's "corporate social responsibility agenda" rather than accepting responsibility for taking meaningful steps to eradicate child labour in the Malawi tobacco sector. Conclusion: In Malawi, transnational tobacco companies are using child labour projects to enhance corporate reputations and distract public attention from how they profit from low wages and cheap tobacco.